2020
DOI: 10.1007/s10571-020-00997-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-visual Opsins and Novel Photo-Detectors in the Vertebrate Inner Retina Mediate Light Responses Within the Blue Spectrum Region

Abstract: In recent decades, a number of novel non-visual opsin photopigments belonging to the family of G protein-coupled receptors, likely involved in a number of non-image-forming processes, have been identified and characterized in cells of the inner retina of vertebrates. It is now known that the vertebrate retina is composed of visual photoreceptor cones and rods responsible for diurnal/color and nocturnal/black and white vision, and cells like the intrinsically photosensitive retinal ganglion cells (ipRGCs) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 258 publications
(406 reference statements)
0
24
0
Order By: Relevance
“…The S-cone influence on melanopic effects is not undisputed, however, as Spitschan et al [ 68 ] found no evidence for the influence in acute neuroendocrine and alerting responses. A more far-fetched, but possible, mechanism is the influence of other opsin types in the retina, such as neuropsin (Opn5), which have been found in the retina of vertebrates (for a review see Guido et al [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The S-cone influence on melanopic effects is not undisputed, however, as Spitschan et al [ 68 ] found no evidence for the influence in acute neuroendocrine and alerting responses. A more far-fetched, but possible, mechanism is the influence of other opsin types in the retina, such as neuropsin (Opn5), which have been found in the retina of vertebrates (for a review see Guido et al [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…The S-cone influence on melanopic effects is not undisputed, however, as Spitschan et al (63) found no evidence for the influence in acute neuroendocrine and alerting responses. A more far-fetched, but possible, mechanism is the influence of other opsin types in the retina, such as neuropsin (Opn5), which have been found in the retina of vertebrates (for a review see Guido et al (64).…”
Section: Discussionmentioning
confidence: 99%
“…Last, but not least neurons in the brain expresses endogenous photoreceptors which are similar structurally and functionally to retinal rhodopsin [encephalopsins ( Blackshaw and Snyder, 1999 )]. Such non-visual opsins play a role in circadian rhythms and regulates physiologically relevant metabolic processes such lipolysis in relation to hibernation ( Guido et al, 2022 ). Having said this, a possible neuromodulatory role of non-visual opsins has yet to be shown, neither it is clear whether non-visual opsins absorb NIR at the power present to the skull).…”
Section: The Relatively Unexplored Issues Of Phototoxicity Photobleac...mentioning
confidence: 99%